Strategies and Challenges for Economic Resilience in the Era of Asymmetric Warfare - Achmad Mirza Apriansyah; Mhd. Halkis; Rudy Sutanto (Formosa Journal of Multidisciplinary Research, 2024)
The research, titled "Strategies and Challenges for Economic Resilience in the Era of Asymmetric Warfare," is motivated by the fact that technological developments and economic globalization promote economic growth in various countries, but as this infrastructure grows, it also creates vulnerabilities that can be exploited, especially in the era of asymmetric warfare. Asymmetric warfare in the economic sector is due to the fact that many aspects of the economy depend on information technology. Digital infrastructure, such as communications networks and information systems, is vulnerable to attacks. These attacks can be physical, such as sabotage of vital facilities, or digital, such as cyber-attacks on energy networks or financial systems, which are part of asymmetric warfare. This is what gives rise to the need for an economic defense strategy to face the challenges that exist in the era of asymmetric warfare. So, it is necessary to identify and analyze the role of the economy in facing current challenges.